(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Murraya koenigii fruits extract was prepared and investigated for repeated dose toxicity in male and female rats. Three different doses at 250, 500, and 750 mg/kg of ethanolic extract of Murraya koenigii fruit were administered daily to groups of 10 animals (five males and five females) for 28 days. A control group received the vehicle (0.5% CMC). Various biochemical parameters, including RBC, WBC, glucose, haemoglobin, cholesterol, creatinine, bilirubin, SGPT, and SGOT, were measured across all groups. In addition, physiological parameters such as daily food intake, weekly body weight, visual and auditory function, and organ weights were recorded. The results indicated that none of the animals in any dose group exhibited test material-related changes in RBC, WBC, creatinine, bilirubin, SGPT, or SGOT. Similarly, no significant changes were observed in physiological parameters like food consumption, visual, or auditory function. However, some changes were noted, including an increase in haemoglobin levels, significant weight loss, and a decrease in cholesterol and glucose levels in the animals. Rats in the 500 mg/kg and 750 mg/kg groups exhibited a loss of subcutaneous fat during the final two weeks of treatment. These groups also showed reductions in total cholesterol and glucose levels, with the most significant effects seen at the 750 mg/kg dose. Based on these findings, the study concludes that the administration of ethanolic Murraya koenigii leaf extract for 28 days increases haemoglobin levels, reduces body weight, subcutaneous fat, and blood glucose levels in medium and high-dose groups.